The Level of Moral Intelligence and its Relationship to Genders and the Educational Stream among High School Students in the North Area of Jordan Valley - Al-Momani, Abdellateef (Jordan Journal of Educational Sciences, 2015)
The present study aimed at exploring moral intelligence among high school students and the effect of educational stream and gender on moral intelligence the sample consisted of (408) males and females to achieve the objectives of the study, the Moral Intelligence Scale developed by Al-Naser (2009) was used after the validity and reliability were constructed Results showed a moderate level of moral intelligence in the total score and for all sub-scores for the domains except the empathy domain, which was high. Also, there was a significant effect for gender on moral intelligence for the total score and for sub-score in the conscience, respect, kindness, tolerance, and fairness domains. The effect was not significant for the empathy and self-control domains. The educational stream had a significant effect on moral intelligence for the total score and sub-score for all domains. Furthermore, there was no significant effect for interaction between gender and educational stream in terms of the total scores and the empathy, conscience, self-control, kindness and fairness domains, while there was a significant effect for the self-control and respect domains